2022
DOI: 10.3390/ma15196801
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Fused Deposition Modeling of Polyetheretherketone (PEEK) and Interest for Dental Restorations: A Systematic Review

Abstract: The aim of this systematic review was to determine the optimal printing parameters for the producing of fused deposition modeling (FDM) 3D-printed polyetheretherketone (PEEK) elements with mechanical properties suitable for dental restorations. Indeed, the mechanical properties are a critical prerequisite for the study of other parameters, such as physical, aesthetic and biological properties. An exhaustive electronic search was carried out in the PubMed, Embase and Web of knowledge databases to gather all the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…The mechanical properties for PLA materials fabricated with FDM technology such as tensile strength, tensile modulus and elongation are reported at a range of 15.5–72.2 MPa, 2.02–3.55 GPa and 0.5–9.2%, respectively [ 36 ]. Similarly, other authors have reported the elastic modulus of polyetheretherketone for dental restoration via FDM at 3–4 GPa [ 37 ]. The ASTM standard reported the minimum and maximum range for the ultimate tensile strength, elongation and compressive strength at 36–71.62 MPa, 3–20% and 41.26 MPa, respectively.…”
Section: Discussionmentioning
confidence: 69%
“…The mechanical properties for PLA materials fabricated with FDM technology such as tensile strength, tensile modulus and elongation are reported at a range of 15.5–72.2 MPa, 2.02–3.55 GPa and 0.5–9.2%, respectively [ 36 ]. Similarly, other authors have reported the elastic modulus of polyetheretherketone for dental restoration via FDM at 3–4 GPa [ 37 ]. The ASTM standard reported the minimum and maximum range for the ultimate tensile strength, elongation and compressive strength at 36–71.62 MPa, 3–20% and 41.26 MPa, respectively.…”
Section: Discussionmentioning
confidence: 69%
“…Zirconia, a dental ceramic crown material, has superior properties of strength and durability when compared to all-ceramic crowns. A randomized controlled trial conducted in 2017 [ 9 ] concluded that the crown of this material fared just as well as metal-based crowns, with studies confirming that the material has relatively less cytotoxic effects [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…An interesting example is the use of PEEK or similar materials that can easily reproduce the structure of bone, but their use involves a complicated and expensive process. [42][43][44] An interesting possibility is offered by bone tissue printing for the fabrication of fractured parts that should be removed or low in bone density through 3D Bioprinting. 45,46 Another improvement concerns the use of an optimized infill for printing bone that is more accurate than the one used and more like a trabecular structure so that it is visually increasingly accurate and close to reality.…”
Section: Discussionmentioning
confidence: 99%